The Relevance of Modern Islamic Boarding Schools with Ulama Cadre According to Imam Zarkasyi (1910-1985) - Yusutria, Yusutria; Kistoro, Hanif Cahyo Adi; Azwar, Azwar (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Imam Zarkasyi was a figure who gave birth to the modern pesantren and ulama cadre in Indonesia. This review is based on literature research with a historical approach. The sources of information depart from the biography and the concept of thought, the methods and information instrumentation from books, papers, posts, magazines, websites, and other types of documentation. The information was analyzed using management systems that can draw information from documentation. Relevant data sourced from works on the topic were analyzed descriptively. The research results are 1) based on "Pondok Modern Synthesis," 2) aiming to produce students who are ready for society, 3) changing the traditional integrity system to the classical boarding school system, 4) presenting educational methods with direction, training, assignments, habituation, guards, role model, and approaches, 5) integrating curriculum with religious material, general material, and language proficiency, 6) forming a waqf body to minimize disputes over ownership and decision making, 7) instilling the psychological value, the Motto of the boarding school, and the philosophy of life, and 8) changing the pattern in appearance from shabby to a modern dress style. This study indicates that modern pesantren as an educational institution has been well-managed and provides great impacts on students or santri as cadres of scholars who are educated to become the next ulama's successors.